Invalidation of the Intracavity Optogalvanic Method for Radiocarbon Detection. Issue 1 (9th February 2016) - Carson, Cantwell G; Stute, Martin; Ji, Yinghuang; Polle, Roseline; Reboul, Arthur; Lackner, Klaus S
Abstract: The intracavity optogalvanic spectroscopy (ICOGS) method has been reported to quantify radiocarbon at subambient levels (<1 part per trillion). ICOGS uses a gas sample that is ionized in a low-pressure glow discharge located inside a 14 CO2 laser cavity to detect changes in the discharge current under periodic modulation of the laser power to determine the 14 CO2 concentration of the sample. When claims of detection thresholds below ambient levels were not verified by other researchers, we constructed a theoretical analysis to resolve differences between these conflicting reports and built and tested an ICOGS system to establish a lower limit of detection. Using a linear absorbance model of the background contribution of 12 CO2 and data from the HITRAN database, we estimate that the limit of detection (3 σ x ) is close to 1.5×10 4 Modern. By measuring a 1.5×10 4 Modern enriched CO2 sample in a cavity modulation ICOGS system without a clear signal, we conclude that for this system the limit of detection for ICOGS must be above 1.5×10 4 . The implications for previous ICOGS reports are discussed.